Stable and unstable grade II syndesmotic injuries require different treatment strategies and vary in functional outcomes: a systematic review. Issue 4 (15th June 2016) - Lubberts, Bart; van Dijk, Pim A D; Donovan, Nathan; van Dijk, C Niek; Calder, James D
Abstract : Importance: Appropriate management of syndesmotic injuries enables athletes to return earlier to play. Currently, there is no best evidence-based management of grade II syndesmotic injuries available. Objective: We conducted a systematic review to identify the current available evidence if either conservative or surgical treatment of grade II ankle syndesmotic injuries leads to improved functional outcomes. Evidence review: A review of the literature was performed according to the PRISMA guidelines. PubMed, EMBASE and the Cochrane Library were searched from January 1962 to 11 May 2016. Studies were identified by using synonyms for 'ankle syndesmosis', 'injury', 'return to activity' and 'patient-reported outcomes'. Findings: The search yielded 106 reports on PubMed, 74 on EMBASE and 5 on the Cochrane Library. After reading the remaining full-text articles, we included two studies describing conservative treatment and one study evaluating both conservative and surgical treatment of grade II syndesmotic injuries. Conclusions and relevance: Currently, we are unable to adequately differentiate between stable grade II and unstable grade II injuries, and therefore it is unknown which grade II syndesmotic injuries should be treated conservatively and which surgically. Developing arthroscopically assessed validated measurements to define the stable syndesmosis may form part of the evaluation and grading of these injuries, and would be an important first step.